Transfer of technology by German firms - Georg Koopmann; Klaus Matthies (Intereconomics, 1979)
Outside the USA little empirical work has been done to assess the impact of technology transfers on the economic performance of transferring countries. The following considerations are concerned with the transfer of technology by German firms.
Keywords: 330; Technology Transfer